2002
DOI: 10.1242/dev.129.2.421
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Sox9 is required for cranial neural crest development inXenopus

Abstract: The SOX family of transcription factors has been implicated in cell fate specification during embryogenesis. One member of this family, Sox9, has been shown to regulate both chondrogenesis and sex determination in the mouse embryo. Heterozygous mutations in Sox9 result in Campomelic Dysplasia (CD), a lethal human disorder characterized by autosomal XY sex reversal, severe skeletal malformations and several craniofacial defects. Sox9 is also expressed in neural crest progenitors but very little is known about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(39 citation statements)
references
References 73 publications
4
35
0
Order By: Relevance
“…The TF, SOX9, was found to be required for neural crest development [ 162 , 163 ]. Moreover, it was also shown to be expressed during hepatic stellate cell activation and caused type I Collagen production in presence of TGFβ [ 164 ].…”
Section: Other Emt Tfsmentioning
confidence: 99%
“…The TF, SOX9, was found to be required for neural crest development [ 162 , 163 ]. Moreover, it was also shown to be expressed during hepatic stellate cell activation and caused type I Collagen production in presence of TGFβ [ 164 ].…”
Section: Other Emt Tfsmentioning
confidence: 99%
“…2 E’). These phenotypes suggest a possible role for miR-196a and miR-219 in NC development ( Collazo et al., 1993 ; Lukoseviciute et al., 2018 ; Petratou et al., 2021 ; Scerbo and Monsoro-Burq, 2020 ; Spokony et al., 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…The process of NCC induction and specification is complex and requires a specific level of signaling by the BMP, Wnt, FGF, RA, Shh, and Notch/Delta pathways to establish a gene regulatory network that is crucial for determining NCC identity ( Villanueva et al, 2002 ; Monsoro-Burq et al, 2003 ; Wu et al, 2005 ; Theveneau and Mayor, 2012 ; Pla and Monsoro-Burq, 2018 ; Rogers and Nie, 2018 ; Prasad et al, 2019 ). During the early steps of NCC formation, these morphogen pathways work in concert with various NCC transcription factors (TFs) such as snai1 , snai2/slug , sox9 , and twist , to establish the neural plate border, regulate NCC specification, and subsequent NCC migration ( Aybar et al, 2003 ; del Barrio and Nieto, 2002 ; LaBonne and Bronner-Fraser, 1998 , 2000 ; Pla and Monsoro-Burq, 2018 ; Rogers and Nie, 2018 ; Spokony et al, 2002 ). As shown in the previous sections, we found that partial depletion of several 16p12.1-affected genes significantly impacted twist expression patterns and NCC migration in the PAs, and that these defects were not due to changes in NCC proliferation rates.…”
Section: Resultsmentioning
confidence: 99%